CARBON FOOTPRINT OF DRINKING WATER SUPPLY SYSTEM IN INDONESIA (STUDI KASUS: KAWASAN METROPOLITAN REBANA) - Nur Azizah, Jihan
The development of the northern part of West Java is carried out through the development of the REBANA Metropolitan Area, so there is also a need to improve services for the basic needs of the community, one of which is access to safe drinking water through the Drinking Water Supply System (SPAM) which must be in line with low-carbon development. Therefore, a study was conducted to calculate the carbon footprint of SPAM and analyze the factors that could affect the carbon footprint of SPAM in the REBANA Metropolitan Area. SPAM's carbon footprint prediction was carried out using a dynamic system approach. Some of the activities that contribute to SPAM's carbon footprint are the process of providing drinking water by PDAM, and wells; AMDK distribution; provision of refill drinking water; and boil drinking water. Based on the results of the sensitivity test, the electricity consumption from the industrial sector's drinking water supply through wells is the most sensitive variable. The model was simulated with data from Indaramayu Regency, and was declared valid with an RMSPE value for the population variable of 0.03%, and for IPA production capacity of 4.89%. The model simulation resulted with KPI Patrol and KPI Losarang data shown that the carbon footprint of SPAM under BAU conditions in 2040 will reach 334,197 tCO2e. Scenario I, II, and III test policies with a water recycling rate, respectively of 10%, 20%, and 30% in 2030. carbon footprint of SPAM in 2040 for scenario I, II, and III, respectively was 285,278 tCO2e, 248,588 tCO2e, and 227,186 tCO2e. Boiled drinking water has the highest carbon footprint per volume unit among other potable water alternatives, which is 122.161 kgCO2e/m3 . Among the drinking water category, drinking water supply from wells for the industrial sector has the highest carbon footprint per unit volume, which is 8.459 kgCO2e/m3. As an effort to reduce SPAM's carbon footprint, a wastewater recycling policy can be implemented as an alternative to drinking water supply through wells, an implementing energy efficiency.